2002
DOI: 10.1073/pnas.222550399
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast FKBP interacts with and affects the accumulation of Rieske subunit of cytochrome bf complex

Abstract: Immunophilins are intracellular receptors of the immunosuppressants cyclosporin A, FK506, and rapamycin. Although all immunophilins possess peptidyl-prolyl isomerase activity and are identified from a wide range of organisms, little is known about their cellular functions. We report the characterization and functional analysis of an FK506 and rapamycin-binding protein (AtFKBP13) from Arabidopsis. The AtFKBP13 protein is synthesized as a precursor that is imported into chloroplasts and processed to the mature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 50 publications
0
77
1
1
Order By: Relevance
“…In this study, we retained the names of published FKBP members in plants. These include regular names such as AtFKBP12 Xu et al, 1998), AtFKBP15-1, AtFKBP15-2 (Luan et al, 1996), and AtFKBP13 (Gupta et al, 2002), and irregular names such as PAS1 and TWD1, which are named according to other circumstances such as phenotype of the mutants (Vittorioso et al, 1998;Kamphausen et al, 2002). For newly identified genes in this study, they were named after the calculated M r of mature proteins predicted from cDNA-deduced sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we retained the names of published FKBP members in plants. These include regular names such as AtFKBP12 Xu et al, 1998), AtFKBP15-1, AtFKBP15-2 (Luan et al, 1996), and AtFKBP13 (Gupta et al, 2002), and irregular names such as PAS1 and TWD1, which are named according to other circumstances such as phenotype of the mutants (Vittorioso et al, 1998;Kamphausen et al, 2002). For newly identified genes in this study, they were named after the calculated M r of mature proteins predicted from cDNA-deduced sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The localization of AtFKBP13 was determined by both import and chloroplast fraction followed by western blot. It was also shown that AtFKBP13 was imported into thylakoid lumen through the DpH pathway (Gupta et al, 2002). Proteomics procedures designed to sequence all thylakoid lumen proteins uncovered several FKBPs including AtFKBP13,18,19,and 22 (Table I and references therein).…”
Section: Genomic Organization and Phylogenetic Relationship Of Arabidmentioning
confidence: 99%
See 1 more Smart Citation
“…With relevance to chloroplast immunophilins, Romano and coworkers further studied the Arabidopsis cyclophilin AtCYP20-2 and show that this cyclophilin may associate with the periphery of PSII supercomplexes (Romano et al, 2004b). Together with earlier reports (Fulgosi et al, 1998;Gupta et al, 2002), these studies suggest that a subset of immunophilins may have specifically evolved to fulfill functions that are unique to photosynthetic organisms. Towards the functional significance of immunophilins in developmental processes, Vespa et al (2004) show that FIP37, an interacting partner for AtFKBP12, is involved in cell division control.…”
Section: A Twist In the Tale: Convergence Of Immunophilins And Ppiasesmentioning
confidence: 79%
“…isoforms (Gupta et al, 2002;Peltier et al, 2002;Schubert et al, 2002). Whilst two of the lumenal immunophilins have been shown to be functionally associated with photosynthetic complex components (Fulgosi et al, 1998;Gupta et al, 2002), the specific function of the majority of chloroplast isoforms remains to be elucidated.…”
Section: A Twist In the Tale: Convergence Of Immunophilins And Ppiasesmentioning
confidence: 99%